Automatic Classification System Color Of Bottle Detection Tool Using Tcs3200 Sensor Based On Arduino - Mulia Supiadi Silalahi; Solly Aryza; Beni Satria (Sean Institute, 2025)
The increasing demand for automation in industries has led to the development of efficient and cost-effective classification systems. This study focuses on designing and implementing an automatic bottle color classification system using the TCS3200 color sensor, integrated with Arduino microcontroller technology. The system aims to detect and classify bottle colors accurately to streamline industrial processes, such as packaging and sorting. The TCS3200 sensor, capable of detecting a wide spectrum of colors, serves as the primary sensing device. It converts light intensity into frequency signals, which are processed by the Arduino microcontroller to determine the color of the bottle. The classification process involves predefined thresholds for Red, Green, and Blue (RGB) components, allowing the system to categorize bottles into specific color groups. Experimental results demonstrate that the system achieves high accuracy in identifying bottle colors under varying lighting conditions. The system is also highly scalable, making it adaptable to different industrial needs. This research concludes that the proposed solution offers a reliable, efficient, and low-cost alternative for bottle color classification in automated industrial applications.